El Comunicador Social como Sujeto del Derecho a la Información: Necesidad o No de la Titulación Universitaria. Caso Córdoba. - Borgarello, Esther Susana; Cipolla , Francisco; Peña, Sebastián; Torres, Valeria (Re-presentaciones: Periodismo, comunicación y sociedad, 2007)
Legal recognition of the professional work, a sense of belonging to a definite group of socially acknowlwdged practitioners and the existence of a certain type of title or academic degree are all essential at the moment of defining what a profession really is. The Journalist statute in Argentina -dictated by Law 12.908- states what a Journalist is upon the basis of a pragmatic hands-on approach that privileges one's ongoing paid working experience over academic university theoric studies. This perspective emphazises that the first option implies embracing a certain active way of living 7-meant to be a vocation- at least one of the many communication media currently at work, that is to say, daily journals, papers, news agencies, radio, cinema, or TV. The same statute gives Journalist status to all the personnel implied at the news gathering and news release process, and to collaborators that at least have published 24 news reports a year in the fields of literature and/or science. It's obvious that, in this context, professional status is acquired through practice and not by university academic training. However, a different trend can be observed nowadays, at least at the field of printed communication media. A majority of people working the are university-degree Journalist, Social Communicators or, at least, students at the very end of their academic university degrees seems to have had an upgrading effect as more people get finally professional Journalist while the average education level of population increases.
Keywords: Qualification of the social communicator; the communicator as university professional; practical journalistic or qualification